Refining the Phenotypic Spectrum of KMT5B-Associated Developmental Delay - Aviva Eliyahu; Aviva Eliyahu; Ortal Barel; Ortal Barel; Lior Greenbaum; Lior Greenbaum; Lior Greenbaum; Gal Zaks Hoffer; Gal Zaks Hoffer; Yael Goldberg; Yael Goldberg; Annick Raas-Rothschild; et al. (Frontiers Media S.A., 2022)
The role of lysine methyltransferases (KMTs) and demethylases (KDMs) in the regulation of chromatin modification is well-established. Recently, deleterious heterozygous variants in KMT5B were implicated in individuals with intellectual disability (ID) and/or autism spectrum disorder. We describe three unrelated patients with global developmental delay (GDD) or ID, macrocephaly and additional features. Using whole exome sequencing, each of the probands was found to harbor a distinct de novo heterozygous disease-causing variant in KMT5B: c.541C > G (p.His181Asp); c.833A > T (p.Asn278Ile); or c.391_394delAAAG (p.Lys131GlufsTer6). We discuss herein their clinical presentations, and compare them to those of previously reported patients. Furthermore, using a three-dimensional computational model of the KMT5B protein, we demonstrate the predicted structural effects of the two missense variants. Our findings support the role of de novo missense and nonsense variants in KMT5B-associated GDD/ID, and suggest that this gene should be considered in the differential diagnosis of neurodevelopmental disorders accompanied by macrocephaly and/or overgrowth.